Neighbourhood influences on mental health in master planned estates: a qualitative study of resident perspectives. (5th December 2014) - Francis, Jacinta; Giles‐Corti, Billie; Wood, Lisa; Knuiman, Matthew
Abstract : Issues addressed: Neighbourhood characteristics have been linked to a range of health outcomes, including mental health. Despite the growth of master planned estates (MPEs) within Australia, few studies have investigated the physical and social correlates of mental health in residents of new housing developments. Methods: This study aimed to identify the facilitators of, and barriers to, mentally healthy neighbourhoods using focus groups with residents of MPEs in metropolitan Perth, Western Australia. Focus group interviews were analysed using qualitative research software package QSR NVivo. Results an. Conclusions: Results suggest that mental health is strongly influenced by a sense of community and security, as well as an aesthetically pleasing environment. Residents of MPEs may experience a strong sense of community due to similarities in life‐stage and the community building efforts of property developers. Expanding population size, social exclusion, and insufficient services may negatively affect the mental health of residents in MPEs. So what?: Identifying correlates of mentally healthy neighbourhoods may help urban planners design residential areas that promote healthy living. Abstract : The proliferation of new housing developments on Australia's urban fringe presents unique opportunities to explore neighbourhoods and mental health. This study investigated the physical and social correlates of mental health in residents of new housing developments and found that mental health was influenced by service availability, security and a sense of community. These findings may help urban planners to design residential areas that promote healthy living.